2016
DOI: 10.1038/nchem.2577
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and structure–activity relationship studies of a series of selective G protein inhibitors

Abstract: G proteins are key mediators of G protein-coupled receptor signalling, which facilitates a plethora of important physiological processes. The cyclic depsipeptides YM-254890 and FR900359 are the only known specific inhibitors of the Gq subfamily of G proteins; however, no synthetic route has been reported previously for these complex natural products and they are not easily isolated from natural sources. Here we report the first total synthesis of YM-254890 and FR900359, as well as of two known analogues, YM-38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(137 citation statements)
references
References 43 publications
3
134
0
Order By: Relevance
“…FR900359 (40,41). In the functional IP-One assay, the L-Orn-induced response of GPRC6A was completely inhibited by 1 M FR900359 (Fig.…”
Section: Co-expression Of the G Q G66d Protein Is Not Mediating Constmentioning
confidence: 99%
“…FR900359 (40,41). In the functional IP-One assay, the L-Orn-induced response of GPRC6A was completely inhibited by 1 M FR900359 (Fig.…”
Section: Co-expression Of the G Q G66d Protein Is Not Mediating Constmentioning
confidence: 99%
“…Based on limited dose response studies (data not shown), mice were injected i.p. with either 0.15 mg/kg of the selective Gα 11/q inhibitor YM-254890 (24), which was diluted in 0.27% DMSO, or an equal volume of 0.27% DMSO as the vehicle control. Blood was taken from the superficial temporal vein at baseline, 4, and 24 hours after injection, and ionized calcium, PTH, and phosphorous were measured as previously described (43).…”
Section: Methodsmentioning
confidence: 99%
“…NPS 2143 hydrochloride (2-Chloro-6-[ (2R)-3-[[1,1-dimethyl-2-(2-naphthalenyl)ethyl] amino]-2-hydroxypropoxy]-benzonitrile hydrochloride) was obtained from Sigma-Aldrich (catalog SML0362) and dissolved in a 20% aqueous solution of 2-hydroxypropyl-β-cyclodextrin (Sigma-Aldrich, catalog H107) prior to use in in vitro studies, as described (21,25). YM-254890 was synthesized as previously described (24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations